(untitled) (REMUNOM, 2026)
Objetivo: O estudo tem como objetivo mapear evidências sobre a utilização de cartilhas educativas em saúde mental para a redução de danos relacionados ao consumo abusivo de álcool e outras drogas. Método: Foi conduzida uma revisão de escopo com buscas realizadas nos sites PubMed, Scopus, SciELO, Web of Science e BVS, nos idiomas português, inglês ou espanhol, que traziam como temas textos que avaliaram cartilhas educativas voltadas à redução de danos. Results: The reviewed studies indicated consensus regarding the effectiveness of the booklets, with an increase in scores for understanding harm reduction concepts. Materials with contextualized visual elements showed adherence nearly twice as high compared to other technologies. The printed format had a higher rate of complete reading. Integrating the booklets into care workflows increased return visits to services. A slight reduction was observed in the frequency of episodes of abusive consumption and a small percentage in expenses related to emergency care. Final considerations: Educational booklets proved to be effective strategies for harm reduction, especially when culturally adapted and integrated into health services. It is recommended to develop national guidelines to standardize the production, distribution, and continuous evaluation of these materials.